SIMPLIFIED LIQUID-LIQUID EXTRACTION METHOD COUPLED WITH LC/DAD BY QUANTITATIVE DETERMINATION OF RISPERIDONE IN HUMAN SERUM - Mennickent, Sigrid; De Diego, Marta; Liser, Bernd; Trujillo, Lina (Journal of the Chilean Chemical Society, 2019)
Risperidone, an antipsychotic drug, was determined in human serum, using an optimized liquid-liquid extraction for isolation from biological fluid, with ethyl acetate as extraction solvent. This sample extraction method was chosen to increase extraction efficiency and reduce matrix interferences. Quantitation was achieved by LC/DAD at 294 nm over the concentration range of 1 ng/mL to 60 ng/mL (r=0.999). Desipramine was used as internal standard (tR for Risperidone: 4.23; tR Desipramine: 7.31). Mobile phase was water: acetonitrile: triethilamine: glacial acetic acid (70:29.16:0.52: 0.33 v/v), using a Purosphere STAR RP-18e 250 x 4.5 mm (5μ) column. RSD, for the intra-assay study, was between 0.52 % - 2.09 % (n=3), and between 0.79 % -3.25 % (n=9) for the inter-assay. LOD was 0.40 ng/mL and LOQ was 0.87 ng/mL. Recovery percentage for the accuracy study was between 90.82% and 98.56% ((RSD ≤ 3.93). The method is simple, fast, precise, accurate, sensible and selective. This method was successfully applied to quantify risperidone in patient serum samples. In conclusion, the method is useful for quantitative determination of risperidone in human serum.